Nação de povos sem história? Impropriedades do primitivismo na recepção do "Manifesto da Poesia Pau-Brasil". - Cardoso, Rodrigo Octávio (Luso-Brazilian Review, 2025)
A defining moment in the quest for a modern national aesthetic unfolded with the publication of Oswald de Andrade's "Manifesto da Poesia Pau-Brasil" in 1924. This event marked a critical juncture in the discourse on shaping a distinctly Brazilian modernism. Andrade's swift avant-gardist language, his call for a national poetics, and his references to Brazilian history provoked strong reactions within modernist circles, particularly regarding Andrade's perceived adoption of primitivism as a way to reference Brazilian culture. This study engages in a cross-referenced examination of the critical reception by key modernist figures of the time, such as Graça Aranha, Tristão de Athayde, Menotti del Picchia, and Mário de Andrade, as well as of Andrade's subsequent publication of the poetry collection Pau-Brasil , mapping the dispersion and regularities in discourses [End Page 134] regarding the development of an authentic national aesthetic in dialogue with the tradition of romantic literary nationalism and revealing the underlying racial subtext that grounds its interplay between modernity and primitivism.